Failure of drug-coated balloon angioplasty to treat bare metal in-stent restenosis accompanied by late stent thrombosis but successful treatment of binary in-stent restenosis. Issue 3 (September 2019) - Shimizu, Takuya; Obata, Jun-ei; Umetani, Ken; Kugiyama, Kiyotaka
Abstract: Drug-coated balloons (DCB) are effective in treating in-stent restenosis (ISR) with neointimal proliferation after bare-metal stent (BMS) implantation, but it is unclear whether DCB are effective in treating BMS-ISR accompanied by thrombosis. An 84-year-old man with previous inferior myocardial infarction and atrial fibrillation developed acute myocardial infarction (AMI) during hospitalization for intracerebral hemorrhage. Emergent coronary angiography (CAG) revealed severe stenosis of the distal left circumflex coronary artery. We implanted a BMS to avoid long-term triple antithrombotic therapy. He received aspirin, clopidogrel, and rivaroxaban for 1 month and then received clopidogrel and rivaroxaban. Seventy days after BMS implantation, he developed AMI, and emergent CAG revealed occlusion of the BMS due to late stent thrombosis. After thrombus aspiration, intravascular ultrasound showed incomplete neointimal healing in the proximal portion of the stent and excessive neointimal proliferation in the distal portion of the stent. DCB angioplasty of the entire BMS was performed after scoring balloon pre-dilation. Seven months after BMS implantation, follow-up CAG revealed binary ISR. DCB angioplasty of the entire BMS was performed again after scoring balloon pre-dilation. Thirteen months after BMS implantation, follow-up CAG did not reveal recurrence of ISR. <Learning objective: Drug-coated balloons (DCB) were ineffective when there was excessive neointimal proliferation accompanied by thrombosis, but effective in binary in-stent restenosis (ISR). DCB may be ineffective in early ISR after bare-metal stent implantations and when there is excessive neointimal proliferation accompanied by thrombosis. Since the safety and efficacy of DCB to treat excessive neointimal proliferation occurring with late stent thrombosis is unclear, further studies are needed.>